2019
DOI: 10.1111/eos.12640
|View full text |Cite
|
Sign up to set email alerts
|

Effect of endomorphin‐2 on orofacial pain induced by orthodontic tooth movement in rats

Abstract: Endomorphin‐2 demonstrates potent antinociceptive effects in various pain models. The objectives of the present study were to explore the role of endomorphin‐2 in the modulation of orofacial pain induced by orthodontic tooth movement in rats. An orthodontic pain model was established in male Sprague‐Dawley rats by ligating coiled springs to mimic orthodontic force (40 g). On days 0, 1, 3, 5, 7, and 14 following orthodontic tooth movement, bite force was recorded as a surrogate measure of orthodontic pain. Ipsi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 51 publications
0
7
0
Order By: Relevance
“…Here, we found that the mechanical hypersensitivities were significantly enhanced in the post‐operative period (days 1 to 9), with a peak on post‐operative day 3. There were limited studies on the mechanical sensitivity of ETM model, and the results of these studies are not completely consistent, which may be related to the following factors such as the force application device, the force application method or the force magnitude 14,22,23 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Here, we found that the mechanical hypersensitivities were significantly enhanced in the post‐operative period (days 1 to 9), with a peak on post‐operative day 3. There were limited studies on the mechanical sensitivity of ETM model, and the results of these studies are not completely consistent, which may be related to the following factors such as the force application device, the force application method or the force magnitude 14,22,23 …”
Section: Discussionmentioning
confidence: 99%
“…There were limited studies on the mechanical sensitivity of ETM model, and the results of these studies are not completely consistent, which may be related to the following factors such as the force application device, the force application method or the force magnitude. 14,22,23 Orthodontic pain is regarded as an inflammatory pain induced by orthodontic force. Inflammatory mediators act on nociceptive nerve endings to sensitize the afferent pulse and lower neuronal excitation threshold, leading to the hyperalgesia development.…”
Section: Discussionmentioning
confidence: 99%
“…An early chromatography study suggested the distribution of enkephalin precursor proteins in the nuclear, microsomal, and supernatant fractions of rat dental pulp tissue ( Wei et al, 1991 ). Another immunostaining assay has shown that endomorphin-2 is basally expressed in TG, trigeminal nucleus caudalis, and periodontium in rats ( Liu et al, 2019 ). Moreover, clinical studies have revealed increased expression levels of β-endorphins and Met-enkephalin in human dental pulp with asymptomatic inflammation or controlled orthodontic intrusive forces by radioimmunoassay ( Chavarría-Bolaños et al, 2014 , 2015 ).…”
Section: Modulation Of Orofacial Pain Via Pors and Eopsmentioning
confidence: 99%
“…Moreover, clinical studies have revealed increased expression levels of β-endorphins and Met-enkephalin in human dental pulp with asymptomatic inflammation or controlled orthodontic intrusive forces by radioimmunoassay ( Chavarría-Bolaños et al, 2014 , 2015 ). The administration of endomorphin-2 to both TG and periodontal tissues alleviates orofacial pain induced by tooth movement ( Liu et al, 2019 ). Local overproduction of PENK-derived peptides in TG sensory neurons via a genomic herpes simplex virus-derived vector evokes a potent antiallodynic effect on trigeminal neuropathic pain by activating PORs ( Meunier et al, 2005 ).…”
Section: Modulation Of Orofacial Pain Via Pors and Eopsmentioning
confidence: 99%
“…As is well documented, orofacial pain sensation is initiated at periodontal sensory terminals, modulated at trigeminal ganglia (TG), replayed at trigeminal nucleus and nally reaches sensory cortex via thalamus (2). Particularly, TG undergo dramatic adaptations in response to orofacial pain (3,4). Speci cally, abundant proteins are upregulated and downregulated in concert to modulate orofacial pain (5,6).…”
Section: Introductionmentioning
confidence: 99%